Experimental research on direct expansion heat pump flue gas waste heat recovery and humidification nitrogen reduction system - Zhang, Qunli; Huang, Haotian; Zhai, Hongbao; Zhao, Wenqiang; Lü, Xiaoshu (Elsevier, 2023)
In order to solve the heat loss and the pollution of gas boilers, a synergistic system consisting of waste heat recovery tower and air humidification tower is proposed. Increasing in moisture content of the air can inhibit the generation of nitrogen oxides and increase the dew point of the flue gas, which is beneficial to the utilization of the waste heat from the flue gas. More heat is absorbed by the humidification water at the fin heat exchanger after the flue gas enters the waste heat recovery tower, which enhances the heat and mass exchange process in the air humidification tower. But the performance of the heat pump was found to show a downward trend, indicating a competitive relationship between nitrogen oxides reduction and waste heat recovery. Under the optimal condition, the experimental system can reduce nitrogen oxides emissions by 62.35%, and the exhaust gas temperature can be reduced to 24.46 °C. The heat pump can recover 6.94% heat while maintaining a minimum nitrogen oxides emission of 39.66 mg/m3. The heat pump makes more heat from the fuel to enter the heating network, which improves the heating efficiency of the boiler system. The system can meet the high-efficiency and clean production requirements of the energy system at the same time.
Keywords: Gas boiler; Combustion-air humidification; Waste heat recovery; NOx emission reduction; Synergy; fi=Energiatekniikka|en=Energy Technology|